Poppy and Max and the big wave - Grindley, Sally; Gardiner, Lindsey (London : Orchard Books, 2008)
Poppy and Max go to the beach where she plans to surf while he chases crabs on the sand, but when one crab gets very close to the water, Max finds himself surfing after all.
"Orchard colour crunchies"--Cover p. [4].
1.7
K-3
Keywords: Beaches -- Juvenile fiction; Dogs -- Juvenile fiction; Surfing -- Juvenile fiction; Beaches -- Fiction; Dogs -- Fiction; Surfing -- Fiction; Beaches -- Fiction; Dogs -- Fiction; Surfing -- Fiction